1996
DOI: 10.1300/j082v30n03_02
|View full text |Cite
|
Sign up to set email alerts
|

ææPhysical Attractiveness StereotypeÆÆ and the Attribution of Homosexuality Revisited

Abstract: The present study investigated whether subjects would perceive male and female faces as homosexual based upon facial attractiveness while statistically controlling for facial masculinity/femininity. Also of interest was the extent to which the subjects' gender and attitudes toward homosexuality would influence their perceptions. Eighty undergraduates indicated how likely they thought it was that six male and six female faces were homosexual. The targets were also rated on attractiveness and masculinity/feminin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In contrast, researchers disagree about how masculinity and femininity cues contribute to male facial attractiveness (Fink & Penton-Voak, 2002), and the desired cues appear dependent on the short- or long-term nature of the relationship and the phase of a woman's ovulatory cycle (e.g., Johnston, Hagel, Franklin, Fink, & Grammer, 2001). Specifically, several studies found that adults perceive masculine male faces as attractive (Brown, Cash, & Noles, 1986; Cunningham, Barbee, & Pike, 1990; Dunkle & Francis, 1996; Grammer & Thornhill, 1994; Johnston et al, 2001; O'Toole et al, 1998; Penton-Voak et al, 2001; Scheib, Gangestad, & Thornhill, 1999), but other studies found that adults perceive feminine male faces as attractive (Dunkle & Francis, 1990; Little, Burt, Penton-Voak, & Perrett, 2001; Little & Hancock, 2002; Penton-Voak et al, 2003; Perrett et al, 1998; Rhodes, Hickford, & Jeffery, 2000). Our interest lies in exploring why these inconsistencies occur, so that we can better understand the contribution of masculinity and/or femininity to male facial attractiveness.…”
mentioning
confidence: 99%
“…In contrast, researchers disagree about how masculinity and femininity cues contribute to male facial attractiveness (Fink & Penton-Voak, 2002), and the desired cues appear dependent on the short- or long-term nature of the relationship and the phase of a woman's ovulatory cycle (e.g., Johnston, Hagel, Franklin, Fink, & Grammer, 2001). Specifically, several studies found that adults perceive masculine male faces as attractive (Brown, Cash, & Noles, 1986; Cunningham, Barbee, & Pike, 1990; Dunkle & Francis, 1996; Grammer & Thornhill, 1994; Johnston et al, 2001; O'Toole et al, 1998; Penton-Voak et al, 2001; Scheib, Gangestad, & Thornhill, 1999), but other studies found that adults perceive feminine male faces as attractive (Dunkle & Francis, 1990; Little, Burt, Penton-Voak, & Perrett, 2001; Little & Hancock, 2002; Penton-Voak et al, 2003; Perrett et al, 1998; Rhodes, Hickford, & Jeffery, 2000). Our interest lies in exploring why these inconsistencies occur, so that we can better understand the contribution of masculinity and/or femininity to male facial attractiveness.…”
mentioning
confidence: 99%
“…For example, Nash, Fieldman, and Hussey (2005) demonstrated that sexual orientation might play an important role in the perception of attractiveness, especially for women. However, Regan, Medina, and Joshi (2001) concluded that, similar to heterosexual counterparts, homosexual individuals desire high levels of physical attractiveness in their sexual partners, and Dunkle and Francis (1996) found that attitudes toward homosexuality do not affect evaluations of attractiveness. Regarding safer sex practices, Kelaher et al (1994) concluded that, in a homosexual sample, 30% of the variance that explained sexual risk taking behaviors could be accounted for by situational behaviors such as partner attractiveness.…”
mentioning
confidence: 99%
“…For the scale evaluation process, we chose to rate the quality of evidence related to the AERA/APA/NCME domains (content/validity/reliability/internal structure) in Likerttype scale. The instruments were rated on a 10 point-scale, punctuating-regardless of the number of studies-if they Rolfs, & Pucell (2007) Nursing students and faculty teachers 4 Cole, Reece, & Lindeman (2005) Health students 5; 10 Span & Vidal (2003) Undergraduate students 3; 4 Burt & DeMello (2002) Undergraduate students 5; 7 Sakalli (2002) Turkish undergraduate students 2; 3; 6; 10 Sakalli & Ug urlu (2002) Turkish undergraduate students 2; 3; 7; 8 Guth, Hewitt-Gervais, Smith, & Fisher (2000) Undergraduate and graduate students 9 Lippincott, Wlazelek, & Schumacher (2000) Asian and American undergraduate students 5 Sakalli & Ug urlu (2001) Turkish undergraduate students 2; 3; 8 Schlub & Martsolf (1999) Nurse students 3 Jome & Tokar (1998) Male undergraduate and graduate students 3; 5 Roderick, McCammon, Long, & Allred (1998) Undergraduate students 3; 4 Berkman & Zinberg (1997) Social workers 3; 4 Monroe, Baker, & Rollb (1997) Men (unspecified) 5; 7 Adams, Wright, & Lohr (1996) Heterosexual men 7 Dunkle & Francis (1996) Undergraduate students 3 Hogan & Rentz (1996) Undergraduate students and staff 3 Matchinsky & Iverson (1996) Undergraduate students 3 Riggle, Ellis, & Crawford (1996) College students 7 Pain & Disney (1995) Australian undergraduate students 4; 6; 8; 10 Patel, Long, McCammon, & Wuensch (1995) College students 3 Smith (1993) Psychiatric nurses 5 Hudson & Ricketts (1980) Undergraduate students 1; 2; 3; 5; 6; 8; 10 Attitudes Toward Lesbians and Gays Scale presented evidence in each of the domains described in Table 1, with a reservation that in the last two items (i.e., temporal stability and internal consistency) the scales punctuated if they presented studies that showed good evidence (>.70).…”
Section: Resultsmentioning
confidence: 99%